Infrastructure and ops hour with Sam Newman : audiobook collection 2022 - Newman, Sam (O'Reilly Media, Inc., 2023)
This is the one stop shop for all Infrastructure & Ops Hour interviews in their audiobook format. Keep up-to-date with Sam Newman and his colleagues on their infrastructure and ops journeys.